2009
DOI: 10.1007/s11661-009-9879-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Grain Refinement of Biomedical Co-29Cr-6Mo Alloy during Conventional Hot-Compression Deformation

Abstract: In order to examine the microstructural evolution during hot-compression deformation of the biomedical Co-29Cr-6Mo (weight percent) alloy without the addition of Ni, hot-compression tests have been conducted at deformation temperatures ranging from 1050°C to 1200°C at various strain rates of 10 À3 to 10 s À1 . The grain refinement due to dynamic recrystallization (DRX) was identified under all deformation conditions by means of field-emission scanning electron microscopy/electron backscattered diffraction (FES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 35 publications
2
45
2
Order By: Relevance
“…No martensitic transformation occurred and no thermal " phase existed after cooling, indicating a much more stable phase as compared to that in the CCM alloy without C or N addition, in which over half the phase transformed into " phase by martensitic transformation during a similar rapid cooling process. 13) Although the results are not presented here, after various hot compression processes in the current study, minimal " phase was detected by both XRD and EBSD, indicating the effective stabilization of the phase with the addition of C and N in all cases. …”
Section: Initial Microstructure Of Ccmcn Alloycontrasting
confidence: 52%
See 2 more Smart Citations
“…No martensitic transformation occurred and no thermal " phase existed after cooling, indicating a much more stable phase as compared to that in the CCM alloy without C or N addition, in which over half the phase transformed into " phase by martensitic transformation during a similar rapid cooling process. 13) Although the results are not presented here, after various hot compression processes in the current study, minimal " phase was detected by both XRD and EBSD, indicating the effective stabilization of the phase with the addition of C and N in all cases. …”
Section: Initial Microstructure Of Ccmcn Alloycontrasting
confidence: 52%
“…The mechanical properties were also improved greatly by grain refinement. The dynamic recrystallization (DRX) behavior in this alloy was investigated in detail by Yamanaka et al 7) Their results indicated that the DRX was related to the low SFE of this alloy and the dense planar dislocation structures due to the formation of SFs possibly inducing the grain refinement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, CCM alloys with small grain size have been practically used. 5) It has been reported that hot forging 6) can re ne the CCM grains from an initial size of 40 µm to 0.6 µm. 6) However, grain renement to a nano-scale is dif cult to be achieved by the conventional processing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted on the control of a microstructure by managing its solidi cation conditions such as the scanning speed of the electron beam, scanning pathway, and energy density 8) . Cobalt-chromium-molybdenum (Co-Cr-Mo) alloys have been widely used as implant materials such as arti cial hip joints and knee joints because they have excellent mechanical properties 9) , wear resistance [10][11][12] , corrosion resistance 13) , and biocompatibility. As further improvement of these properties is demanded, more research has been conducted [14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%